Diabetic neuropathy is a generalized phenomenon with impact on hand functional performance and quality of life - Kender, Zoltán; Gröner, Jan; Jende, Johann; Kurz, Felix T.; Fleming, Thomas; Sulaj, Alba; Schuh-Hofer, Sigrid; Treede, Rolf-Detlef; Bendszus, Martin; Szendrödi, Julia; Nawroth, Peter Paul; Kopf, Stefan (European journal of neurology, 2022)
Background and purpose Diabetic sensorimotor peripheral neuropathy is usually considered to affect predominantly the lower limbs (LL-N), whereas the impact of upper limb neuropathy (UL-N) on hand functional performance and quality of life (QoL) has not been evaluated systematically. This study aims to investigate the prevalence and characteristics of UL-N and its functional and psychosocial consequences in type 2 diabetes. Methods Individuals with type 2 diabetes (n = 141) and an age- and sex-matched control group (n = 73) underwent comprehensive assessment of neuropathy, hand functional performance, and psychosocial status. Results The prevalence of UL-N was 30.5% in patients with diabetes and that of LL-N was 49.6%, with 25.5% exhibiting both. Patients with diabetes showed similar sensory phenotype regarding both large and small fiber functions in hands and feet. Patients with UL-N showed reduced manual dexterity, but normal hand grip force. Additionally, there was a correlation between reduced dexterity and sensory deficits. Patients with UL-N had reduced estimates of psychosocial health including health-related QoL compared to control subjects and patients without UL-N. UL-N correlated with the severity of LL-N, but not with duration of diabetes, glycemia, age, or sex. Conclusions This study points to a substantial prevalence of UL-N in type 2 diabetes. The sensory phenotype of patients with UL-N was similar to LL-N and was characterized by loss of sensory function. Our study demonstrated an association of UL-N with impaired manual dexterity and reduced health-related QoL. Thus, upper limb sensorimotor functions should be assessed early in patients with diabetes.